(untitled) (European Journal of Interdisciplinary Studies, 2015)
The revolution of research, precisely, the revolution of knowledge has been transforming the role of modern universities in Europe and farther. Nowadays, it is emphasized the need to revise the whole process of research – technology – production. The enhancement of human knowledge is a consequence of the changes and transformations being done in all aspects of the practical life of the society. A quick development has accompanied the direct or indirect geographical group sciences. Among the widespread fields of study introduced nowadays, it is hard to find another field of study, which is more interdisciplinary than the one being discussed. Albania is trespassing another stage of social and economical transformations, and this is due to political changes undergone in the years 1990-1991. This stage is followed by other new changes which require further scientific studies based on specific topics. An important step has been done in the regional tackling of problems, where it was estimated the interdependence between the geographic environment and the demographic and economic development of specific regions. Such studies have been done in the field of tourism, a field much explored in the aspects of natural and cultural inheritance. The scientific research in Geography needs to be developed through detailed analysis, which is based on primary and secondary data. These data should be well interpreted from a contemporary point of view, characterized also from physical and geographical transformations, as well as social and economical ones. Although the curricula of Geography in Albanian universities has undergone several changes, (a lot of subjects have been added to the curricula), their effect on the scientific research has not been so much reflected. The field of the applicative scientific research in Geography is broad, because the object of Geography is broad. The applicative scientific research of Geography in Albania will give importance to the role of the geographer, especially in different levels of decisions. The paper will show concrete arguments for the necessity of strengthening the applicative character in the scientific research of Geography in our country.